BENEFICIAL EFFECT OF TAMARINDUS INDICA ON THE KIDNEY OF ALBINO RAT AFTER FLUORIDE INTOXICATION - P.K. SINGH,; S. A. MIR, (International Journal of Pharma and Bio Sciences, 2016)
The toxic effects were evaluated of fluoride ingestion on the kidney of the albino rats, and the possible reversal beneficial effect by use of Tamarindus indica. The effect of fluoride intoxication on lipid peroxidation and antioxidant system (SOD, CAT, GST and GR) in the kidney of albino rats were also studied. The body weight, organ weight and body weight – organ weight ratio were decreased significantly due to the side effect of ground water fluoride, while increased due to beneficial effect of T. indica. The lipid peroxidation increased due to the side effect of ground water fluoride; while decreased due to beneficial effect of T. indica. while, SOD, CAT, GST and GR decreased significantly due to the effect of ground water fluoride, while increased due to beneficial effect T. indica. Increased lipid peroxidation and generation of Reactive Oxygen Species (ROS) thus, exerting a toxic effect on proximal tubular cells of the kidney, The effect of fluoride on kidney has two aspects: one is direct action; the other is indirect – disturbances of free radical balance and abnormal of some inorganic elements.